Assessment of life cycle greenhouse gas emissions from horticultural products. Supplementary requirements for the cradle to gate stages of GHG assessments of horticultural products undertaken in accordance with PAS 2050 Part 1, (31st March 2012) - British Standards Institution,
No abstract available